Impact of Conscious Change Management on the Quality of Cluster Management - Młodzianowski, Daniel; Rostek, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The article analyzes the role of change management in efficient functioning of the organization and points to the need of using the new approach of change management in clusters. In order to prove this need, available literature and practical knowledge were reviewed for the presence of the concept and examples of its use in change management in clusters. The main aim of the article is to show that the clusters stop being a group of economic entities uniting to realize only a single project, but more often they become a group of aware cooperators coordinating their actions in a long‑term perspective. This way they achieve much higher level of efficiency and development than single entities.